Model Project-Based Learning Pada Pembelajaran Biologi Materi Keanekaragaman Hayati: Pengaruhnya Bagi Hasil Belajar Siswa SMA Negeri 1 Melonguane - Dea Debora Losoh; Jefry Jack Mamangkey; Meity N. Tanor (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Biology education requires a learning strategy that can improve conceptual understanding while developing students' critical thinking skills. This study aims to analyze the influence of the Project-Based Learning (PjBL) learning model on the learning outcomes of class X students on biodiversity materials at SMA Negeri 1 Melonguane. The research uses a quasi-experimental method with a Pretest-Posttest Control Group Design, involving two classes, namely the X-A experimental class taught using the PjBL model with a mini ecosystem project, and the X-D control class. The control class is taught conventionally. The analysis results showed a significant increase in the posttest score of the experimental class with an average of 79.33 compared to the control class with an average of 73.39. These findings indicate that applying the PjBL model effectively creates active learning, increases student engagement, and develops problem-solving skills and creativity. The lower variability of scores in the experimental class showed that PjBL could accommodate differences in students' abilities. Project-based learning also arouses students' motivation and confidence, making Biology learning more contextual and meaningful. The implications of this study show that applying the PjBL model can be an alternative to Biology learning strategies to improve learning outcomes while supporting the development of 21st century skills. This research enriches the literature on Biology learning innovations. It opens opportunities for further studies related to the application of PjBL to other materials or long-term impact analysis on students' academic achievements.